Advancing Digital Assets: Ethereum-Based NFT Marketplace with Integrated Blockchain Wallet Solutions - S Mohammed Ishaq; Arpitha K M; Himanshu Choubey; Mohammed Azeemulla; Abhist Dubey (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In an increasingly computerized universe, the secure administration & trading of crypto files and documents has become a critical concern. In this estimate seeks to label this issue beside creating decentralized implementation (App) that uses distributed larger technology and deep neural network models to enable secure and efficient digital asset management, with an emphasis on NFTs. The App’s features include secure wallet network, NFT picture production, stamp out, a sale out, and account handling. The App’s backend is built on the Goerli development network with reliability intelligent contracts, while IPFS and ReactJS/Ethers are utilized for scattered storage and client development, individually. Furthermore, the Open AI Api is used to create unique NFT picture depends on customer input. This design showcases the actual application of distributed larger technology and deep neural network models for creating Apps for assured and scattered crypto asset management. Universal, the project adds to the continuing study on blockchain-based solutions for secure digital asset management, while also emphasizing the power of distributed larger technology and deep neural network models to change the way we handle and trade crypto assets.